Hing Production Research in Afghanistan - Zahirian, Gul Ahmad (Journal of Natural Sciences – Kabul University, 2021)
Asafoetida is an oleo-gum-resin obtained from the exudates of the roots of the Iranian endemic medicinal plant, Ferula asafoetida. It is widely used around the world as a flavoring spice in various foods. Traditionally, it has been used for the treatment of a variety of diseases, such as asthma, epilepsy, stomach aches, flatulence, intestinal parasites, weak digestion, and influenza. Recent pharmacological and biological studies have shown that asafoetida possesses several beneficial activities, including antioxidant, antiviral, antifungal, cancer chemopreventive, antidiabetic, antispasmodic, hypotensive, and molluscicidal properties. Given its great medicinal importance, detailed studies of asafoetida are required prior to clinical trials.